Some Reproductive characteristics of Marwari mares - RANGASAMY, A; BANSAL, R S; SHARMA, R C; LEGHA, R A; YASH PAL,; TANDON, S N (The Indian Journal of Animal Reproduction, 2023)
Data on different reproductive traits i.e. length of the estrous cycle, duration of estrus,gestation period and foal heat in respect of Marwari mares for a period of five years (2002-2006)were recorded and analyzed for the present study. These findings may be useful, as ready referencesfor some of the reproductive characteristics of our indigenous horses.
Keywords: Estrus; Estrous cycle; Foal heat; Gestation; Marwari mares